Cultivation of aerobic granular sludge for rubber wastewater treatment - Rosman, Noor Hasyimah; Nor Anuar, Aznah; Othman, Inawati; Harun, Hasnida; Sulong @ Abdul Razak, Muhammad Zuhdi; Elias, Siti Hanna; Mat Hassan, Mohd Arif Hakimi; Chelliapan, Shreesivadass; Ujang, Zaini (Elsevier, 2013)
Aerobic granular sludge (AGS) was successfully cultivated at 27 ± 1 C and pH 7.0 ± 1 during the treatment of rubber wastewater using a sequential batch reactor system mode with complete cycle time of 3 h. Results showed aerobic granular sludge had an excellent settling ability and exhibited exceptional performance in the organics and nutrients removal from rubber wastewater. Regular, dense and fast settling granule (average diameter, 1.5 mm; settling velocity, 33 m h1 ; and sludge volume index, 22.3 mL g1 ) were developed in a single reactor. In addition, 96.5% COD removal efficiency was observed in the system at the end of the granulation period, while its ammonia and total nitrogen removal efficiencies were up to 94.7% and 89.4%, respectively. The study demonstrated the capabilities of AGS development in a single, high and slender column type-bioreactor for the treatment of rubber wastewater